Response of phytoplankton community and size classes to green Noctiluca bloom in the northern Arabian Sea. Issue 1 (April 2018) - Baliarsingh, S.K.; Lotliker, Aneesh A.; Sudheesh, V.; Samanta, Alakes; Das, Sourav; Vijayan, A.K.
Abstract: A comprehensive analysis on the phytoplankton ecology with special reference to different phytoplankton size classes was carried out at green Noctiluca scintillans (hereafter Noctiluca ) bloom and non-bloom locations in offshore waters of the northern Arabian Sea. At the bloom locations, green Noctiluca represented a dense mono-specific proliferation with average cell density of 10.16 ± 5.806 × 10 4 cells-L −1 and relative abundance share of 98.63%. Active photosynthesis through prasinophytic endosymbiont was depicted from net community production magnitude reaching 85.26 mgC/m 3 /Day under low prey abundance. Parallel swarming of Porpita porpita, a voracious copepod feeder signified the competitive advantage of Noctiluca to have the phytoplankton prey. Average concentration of picophytoplankton biomass was eleven times lower in surface waters of non-bloom stations in comparison to bloom. Higher N:P ratio in subsurface waters of non-bloom stations signified non-utilization of nitrogenous nutrients. Green Noctiluca bloom onset subsequent to diatom rich conditions was evident from spatio-temporal ocean colour satellite imageries. Highlights: Picophytoplankton contributed >30% to the total phytoplankton biomass despite green Noctiluca bloom conditions. Restriction of green Noctiluca cells to upper few meters of surface evidenced from taxonomy and primary production. Ecological linkage of Porpita porpita with green Noctiluca ecology. Diatom rich conditions favours onset of green Noctiluca bloom.